Contained Attitudes. - Bos, Saskia; Dercon, Chris (New York : Artists Space, 1986)
Meuser ; Séchas, Alain ; Van Oost, Jan ; Zwerver, Ton ; Bourges, Alain ; Theys, Koen ; Studio's Independent Theatre ; Young, Graham
Contained Attitudes, Artists Space, New York, December 11 1986 - January 24, 1987
boek